(untitled) (NAU Journal of Library and Information Science, 2025)
The development of digital libraries has brought about changes in the mode of service delivery and the way library information is accessed and disseminated. However, their operation is influenced by various factors, including emerging technologies, user needs and organizational contexts. This paper, therefore, discussed the concepts of new age and digital libraries, and the requirements for digital library operations in the new age. It also examined the prospects of digital libraries which focused on the expected roles of libraries/librarians, the quality of information resources and services, access to information resources in digital format, users‟ satisfaction with digital library systems as well as digital preservation of local contents. The challenges affecting the smooth running of digital libraries such as poor funding, lack of digital facilities, inadequate number of librarians with digital technology skills, etc. were highlighted. Suggestions for improvement such as improved funding for libraries, provision of training opportunities for librarians in ICT, acquisition of state-of-the-art facilities, etc. were also provided to ameliorate the situation.